Financial challenges of teaching hospitals and providing solutions - Samaneh Safarani; Hamid Ravaghi; Pouran Raeissi; Mohammadreza Maleki (Wolters Kluwer Medknow Publications, 2018)
INTRODUCTION: Hospitals are one of the most important institutions in providing health-care services. Highly experienced specialists, advanced technology, and decisive decisions about patients' deaths and lives are all gathered in a dynamic and unique organization called Hospital. A huge portion of human, financial, and equipment resources are allocated to teaching hospitals; however, these hospitals are always faced with a lack of funding. The purpose of this study was to investigate the financial challenges of teaching hospitals and providing solutions. MATERIALS AND METHODS: A qualitative study was conducted using face-to-face interviews with a purposeful sample of 37 top and middle managers in the level of the Ministry of Health, its universities, teaching hospitals, and its affiliated departments in Tehran. Thematic analysis approach was used to analyze the data by applying MAXQDA10 software. RESULTS: Six themes among the reasons for financial challenges in teaching hospitals were insufficient funding for the educational and research sections and paying more attention to treatment, increased financial burden due to presence of medical student, indigent patients, disability in budget managing due to their dependence on medical universities, relative autonomy of hospitals, and payment systems. Among other factors, there are also insurance problems arisen from increased deductions on bills due to insurance astringency and delayed payment. CONCLUSION: The findings of the present study indicated that the major financial challenges of teaching hospitals faced severe financial problems, which had a negative effect on their entire activities and led to weakness in the implementation of their missions. Considering budget division among three defined missions of teaching hospitals (treatment, research, and education), the largest share of budget was allocated to treatment. Therefore, an appropriate and definite budget division is suggested to improve the allocation of resources to all three missions and to enhance staff's and patients satisfaction.